2016
DOI: 10.1021/acs.joc.6b01933
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II)-Catalyzed Bidentate Directing Group-Aided Chemoselective Acetoxylation of Remote ε-C(sp2)–H Bonds in Heteroaryl–Aryl-Based Biaryl Systems

Abstract: In this Article, we report our successful attempt on the Pd(II)-catalyzed, bidentate directing group-aided, chemoselective acetoxylation/substitution of remote ε-C(sp)-H bonds using heteroaryl-aryl-based biaryl systems. While the bidentate directing group (BDG)-aided, C-H activation, and functionalization/acetoxylation of the β-, γ-, and δ-C-H bonds of the appropriate carboxamide systems were well documented, there exist only rare reports dealing with the C-H activation and functionalization of remote ε-C-H bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 115 publications
1
14
0
Order By: Relevance
“…of TEMPO, which gave the product 20 a in 67% yield (Scheme ). In concurrence with the literature reports, this reaction indicated that perhaps the sp 2 δ ‐C−H intramolecular amidation/annulation of the substrates 12 and 19 did not proceed via the single electron transfer (SET) or free radical pathway …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…of TEMPO, which gave the product 20 a in 67% yield (Scheme ). In concurrence with the literature reports, this reaction indicated that perhaps the sp 2 δ ‐C−H intramolecular amidation/annulation of the substrates 12 and 19 did not proceed via the single electron transfer (SET) or free radical pathway …”
Section: Resultssupporting
confidence: 90%
“…of PIDA and Pd[OAc] 2 (5 mol%) found to afford the thieno[2,3‐ c ]quinolin‐4(5 H )‐one derivative 20 a in a maximum of 94% yield (entry 2, Table ). It is to be noted that the C(2)/C(5)‐H bond of thiophene/furan systems is known to undergo the direct C−H functionalization (e. g., arylation and acetoxylation) . However, the other possible by‐product e. g., the C−H acetoxylated product 21 was not obtained from 19 a under the present experimental conditions.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, functional group assisted selective acetoxylation of inert C−H bonds of an aryl system with the help of transition metal catalyst has proven to be a highly diligent approach for the direct construction of C−O bonds …”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41][42] Moreover, functional group assisted selective acetoxylation of inert CÀ H bonds of an aryl system with the help of transition metal catalyst has proven to be a highly diligent approach for the direct construction of CÀ O bonds. [43][44][45][46][47][48][49][50][51] Taking an impetus from the enduring development of selective acetoxylation of CÀ H bonds and following our interest for the selective functionalization of valuable heterocyclic organic molecules (Scheme 1), [52][53]…”
Section: Introductionmentioning
confidence: 99%